Studi Komparasi Kemampuan Representasi Matematis Antara Model Pembelajaran Connected Mathematics Project dan Problem Based Learning - Githa Niermala Riescillia; Lusiana Prastiwi; Muhajir; Siti Musrifah (Jurnal LENTERA: Jurnal Studi Pendidikan, 2023)
This study aims to determine whether there are differences in the ability of mathematical representation between students who get learning using the Connected Mathematics Project learning model and students who get learning using the Problem Based Learning model. The sample of this research is class VIIIA and VIIIB students at SMPN 18 Surabaya. The approach used is an experimental approach. The research instrument consisted of a pretest and posttest which contained questions to find out students' mathematical representation abilities (visual, verbal, and symbolic representation abilities) on flat sided geometric material. This type of research is quantitative where the method of data analysis uses statistical analysis of data normality tests, homogeneity, and independent sample t-test with SPSS 21 software. The results show that there are differences in the Connected Mathematics Project learning model and the Problem Based Learning Model on the ability of mathematical representation of the subject matter construct flat sided rooms in class VIII SMPN 18 Surabaya and overall the average scores for CMP and PBL classes have a significant difference (p = 0.006). It can be concluded that the CMP and PBL learning models can improve students' mathematical representation abilities